TATA KELOLA BUMDESA BINA NEGERI DI DESA GUNUNG SAHILAN KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR TAHUN 2024 - Suheri, Ramadhan; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study aims to analyze the governance of the Village-Owned Enterprise (BUMDesa) Bina Negeri in Gunung Sahilan Village, Gunung Sahilan District, Kampar Regency. BUMDesa plays a strategic role in supporting rural development and improving community welfare. Although BUMDesa Bina Negeri has operated since 2011 and manages several business units, its implementation still faces challenges, particularly low community participation and the suboptimal utilization of village assets and potential. This research employs a qualitative descriptive approach, using primary data obtained through interviews and secondary data collected from relevant documents. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The theoretical framework used is Widyananda’s governance concept, which includes transparency, accountability, fairness, and responsibility. The findings indicate that BUMDesa Bina Negeri has demonstrated a positive commitment to implementing good governance principles; however, weaknesses remain in information access, human resource management, internal control systems, and performance measurement. These results highlight the need to strengthen community participation and optimize village potential to enhance the effectiveness of BUMDesa management. Keywords: Governance, Village-Owned Enterprise (BUMDesa), Transparency, Accountability, Fairness, Responsibility